2018
DOI: 10.1038/s41598-018-33022-9
|View full text |Cite
|
Sign up to set email alerts
|

Towards improvement in prediction of iodine value in edible oil system based on chemometric analysis of portable vibrational spectroscopic data

Abstract: Iodine value (IV) is a significant parameter to illustrate the quality of edible oil. In this study, three portable spectroscopy devices were employed to determine IV in mixed edible oil system, a new Micro-Electro-Mechanical-System (MEMS) Fourier Transform Infrared Spectrometer (MEMS-FTIR), a MicroNIRTM1700 and an i-Raman Plus-785S. Quantitative model was built by Partial least squares (PLS) regression model and four variable selection methods were applied before PLS model, which are Monte Carlo uninformative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The IV represents the degree of unsaturated fats and oils and also indicates the relative content of USFA (Naz et al, 2005). The IV determines the quality and grade of oil and is used as an authentication test in the oil industry (Yan et al, 2018). The IV of animal skin fat in the present study is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The IV represents the degree of unsaturated fats and oils and also indicates the relative content of USFA (Naz et al, 2005). The IV determines the quality and grade of oil and is used as an authentication test in the oil industry (Yan et al, 2018). The IV of animal skin fat in the present study is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The emissive nature of CQDUiO-66 within the device was used for analyzing the quality of edible oils [22] as the current practices for analyzing edible oils [23] involve the use of tedious, costlier processes [24] requiring skilled manpower [25] . The chemical background of edible oils is that they are composed of saturated and unsaturated fatty acids, which contribute to the health benefit of oil.…”
mentioning
confidence: 99%